SIKAP LANSIA SUKU BATAK TOBA DALAM MENGHADAPI KEMATIAN PADA STATUS SAURMATUA DENGAN ANALISIS ETNOGRAFI - , FREDRIK, Prof. Dr. Endang Ekowarni ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study directs our thinking to an ordinary thing we find in our lives that is death. Death is a scary thing. For the Batak Toba Batak in this case the death of the elderly is something that is given as a tribute to the deceased as well as to preserve the culture. This study aims to identify and understand the attitude of the Batak Toba elderly in the face of death on the saurmatua status through well being and successful aging. The number of informants in this study were five elderly Toba Batak tribe who have criteria 1) elderly 2) Toba Batak tribe, 3) has the saurmatua status 4) understand the saurmatua status, 5) participate in the activities of Batak customs, 6) men. Data is collected through interviews, observations, supplemented by interviews significant other. The approach used is qualitative ethnographic methods and techniques of thematic analysis. From this thematic analysis will be obtained cultural themes. The results Toba Batak tribe elderly perception of the status of the death saurmatua in achieving well being can be understood by the meeting of the cognitive component of positive and positive affective component within ES, DH, MM are pushing to have the readiness to face death while LH and T does not have a readiness in the face of death. Perceptions of the elderly on the status of the Batak Toba saurmatua deaths in achieving successful aging can be understood with the fulfillment of the acceptance criteria of health status, personal beliefs (giving meaning to life), social activities, psychosocial support, functional capacity (physical health), relationships with family and friendship good and do not have depression and despair found within ES, DH, LH MM, and T indicating the achievement of successful aging. Achievement of successful aging in the ES, DH, LH, MM and T indicate that they have a readiness to face death.